The current issue of JoS - Paetau, Michael (Journal of Sociocybernetics, 2014)
Deeply shocked we had to take note that Nils O. Larsson, one of the authors of the last issue of Journal of Sociocybernetics, passed away very unexpectedly. Since many years Nils O. Larsson was a member of the Research Committee on Sociocybernetics (RC 51) and the International Sociological Association (ISA). He took part in the World Congress of Sociology 2010 in Gothenburg, where he organized the RC 51 – Session “Global problems require solutions with a global perspective”. This session was strongly related to one of the main themes of the XVII World Congress of Sociology: sustainability, a subject which had become more and more in focus due to the threatening climate change and the present economic crisis. In the face of the increasing and sometimes overwhelming complexity of this problems it was Nils’ ambition to develop an adequate research method that can analyse and design human activity systems on individual, family, as well as society and global level. He called this methodology "Decision Settings Analysis". Three of the papers, presented in his world congress session were published later in Volume 10 of JoS. But it was not granted to Nils that he could lived to see this result of his efforts. He died during the editorial process what came to know to us when the Volume already was published. Today, while we are preparing the VXIII World Congress of Sociology in Yokohama, we miss Nils O. Larsson very much. The current issue of the Journal of Sociocybernetics includes three theoretical oriented articles and one empircal study. In their article